IMPLEMENTATION OF THE COURSE FOR CAREGIVERS OF PATIENTS IN SPECIAL CARE - Mota, Renata Gomes; de Oliveira Marques, Aryadne; de Brito Oliveira, Itala; Gadelha Severino, Fernanda; Soares Moreira Alves, Jamille (Cadernos ESP, 2024)
Train, with theoretical and practical knowledge, informal caregivers of patients in special conditions for the improvement of their daily activities. This is about an action research, held in the years of 2021 and 2023, in a transitional care unit located in the state of Ceará, on the implementation of the "Course for Caregivers of Patients in Special Care". The study population was composed of the caregivers of patients admitted to the institution and the sample consisted on caregivers over 18 years of age and with the minimum education of complete literacy, resulting in 81 people able to participate in the course. In all, in the period of 18 months, 81 caregivers were certified with a workload of 40 hours, and 80% of the vacancies offered were filled. The course played a crucial role in the technical, critical and social improvement of the participants.
Keywords: Health Education; Caregivers; Patient safety